Design of a new optical system to generate narrowband guided waves with an application for evaluating the health status of rail material - Ming Ng, Kim (2019)
he Letter presents a new design of Sagnac interferometer based optical system (SIOS) that emits a line-arrayed pattern generating narrowband high-energy waves in a specimen. The SIOS is further used to excite Rayleigh waves in a pristine rail specimen to evaluate its intrinsic nonlin earity resulting from the lattice anharmonicity and dis solved impurities. Such a nonlinearity appears in the response in the form of a second harmonic that is sensed in this Letter using a scanning laser Doppler vibrometer. In addition to this noncontact measurement, a contact mea surement of the nonlinearity of rail steel using wedge trans ducers is also carried out to compare the performance of the SIOS. Both experimentally evaluated nonlinearities are compared with those obtained using the nonlinear elasticity equations. The close agreement with the theoretically estimated nonlinearity and higher repeatability shows that the SIOS is effective in measuring the intrinsic nonlinearity of the rail steel and, thereby, predicting the health status of the rail specimens before fixing them on the track.